The answer to 19b is 35
i’m sorry i don’t know part A
Answer:
Step-by-step explanation:
y + 6 = -2/3(x + 1)
y + 6= -2/3x - 2/3
y + 18/3 = -2/3x - 2/3
y = -2/3x - 20/3
It is in form
0=ax^2+bx+c
0=-3x^2-2x+6
a=-3
b=-2
c=6
so
x=
x=
x=
x=
x=
x=
x= or
The dog can roam 59.7 feet if the dog is on a 60-foot leash. One end of the leash is tied to Rover, who is 2 feet tall.
<h3>What is the Pythagoras theorem?</h3>
The square of the hypotenuse in a right-angled triangle is equal to the sum of the squares of the other two sides.
We have:
Rover the dog is on a 60-foot leash. One end of the leash is tied to Rover, who is 2 feet tall. The other end of the leash is tied to the top of an 8-foot pole.
After drawing a right-angle triangle from the above information.
Applying Pythagoras' theorem:
60² = 6² + x²
After solving:
x = 59.69 ≈ 59.7 foot
Thus, the dog can roam 59.7 feet if the dog is on a 60-foot leash. One end of the leash is tied to Rover, who is 2 feet tall.
Learn more about Pythagoras' theorem here:
brainly.com/question/21511305
#SPJ1
I tried to answer this question but I can’t find the answer